The Investigation of Anger and Aggression Perception of Athletes in Terms of Various Variables - Ci̇n, Hülya; Yilmaz, Berk Hakan; Ekti̇ri̇ci̇, Arıkan (Manisa Celal Bayar Üniversitesi, 2022)
The aim of this study is to examine the perception of anger and aggression of athletes in terms of various variables. The survey method, one of the quantitative research methods, was used in the study. The participants of this research are 373 (187 female, 186 male) athletes determined by the snowball sampling method. Competitive Aggressiveness and Anger Scale (CAAS) which was developed by Maxwell and Moore (2007) and adapted into Turkish by Gürbüz et al. (2019) was used in this study as data collection tool. As a result of the Cronbach Alpha internal-consistency analysis, the values were calculated as 0.84 for the “Anger” sub-dimension, 0.78 for the “Aggression” sub-dimension, and 0.86 for the overall scale. According to the results of the independent samples t-test for gender and sports branch variables, a significant difference was found between the groups in the aggression sub-dimension (p<0,05). According to the results of the ANOVA test, no significant difference was found in the mother's education level and family monthly income level variables (p>0,05). According to the results of the ANOVA test conducted for the variables father's education level, sports age and the education level of the athlete, a significant difference was found between the groups. The Pearson Correlation Analysis indicated that there was a low level of positive and significant relationship between age and anger (p<0,05). As a result, it has been revealed that the anger and aggression levels of the athletes differ according to the variables of age, gender, sports branch, education level of the athlete, father education level and sports age.

Bu araştırmanın amacı sporcularda öfke ve saldırganlık algısının çeşitli değişkenler açısından incelenmesidir. Araştırmada nicel araştırma yöntemlerinden tarama yöntemi kullanılmıştır. Araştırmanın katılımcılarını kartopu örnekleme yöntemiyle belirlenen 373 (187 kadın, 186 erkek) sporcu oluşturmaktadır. Araştırmada veri toplama aracı olarak Maxwell ve Moore (2007) tarafından geliştirilen, Gürbüz, Kural ve Özbek (2019) tarafından Türkçe’ye uyarlanan Sporda Saldırganlık ve Öfke Ölçeği (SSÖÖ) kullanılmıştır. Cronbach Alpha iç-tutarlılık analizi sonucunda bu değer “Öfke” alt boyutu için 0,84, “Saldırganlık” alt boyutu için 0,78, ölçeğin geneli için ise 0,86 olarak hesaplanmıştır. Cinsiyet ve spor branşına yönelik olarak gerçekleştirilen bağımsız örneklemler t-testi sonucuna göre saldırganlık alt boyutunda gruplar arasında anlamlı farklılık saptanmıştır (p<0,05). Gerçekleştirilen ANOVA testi sonuçlarına göre anne eğitim düzeyi ve aile aylık gelir düzeyi değişkenlerinde anlamlı farklılık tespit edilmemiştir (p>0,05). Baba eğitim düzeyi, spor yaşı ve sporcunun eğitim düzeyi değişkenlerine yönelik olarak gerçekleştirilen ANOVA testi sonuçlarına göre ise gruplar arasında anlamlı farklılık tespit edilmiştir. Yaş değişkeni ile ölçek alt boyutları arasında gerçekleştirilen Pearson Momentler Çarpımı Korelasyon Analizi sonuçlarına göre ise yaş ile öfke arasında düşük düzeyde pozitif ve anlamlı bir ilişki olduğu sonucuna ulaşılmıştır (p<0,05). Sonuç olarak, sporcuların öfke ve saldırganlık düzeylerinin yaş, cinsiyet, spor branşı, sporcunun eğitim düzeyi, baba eğitim düzeyi ve spor yaşı değişkenlerine göre farklılaştığı ortaya konmuştur.
Keywords: Sporcularda öfke; Sporcularda saldırganlık; Fair-play; Futbolcularda saldırganlık; Sporda öfke ve saldırganlık; Anger in athletes; Aggression in athletes; Fair-Play; Aggression in soccer players; Anger and Aggression in sports; Spor Hekimliği; Sports Medicine